PROFIT PLANNING ANALYSIS ON BUSINESS TAHU TEMPE BAIM MANNA SOUTH BENGKULU DISTRICT - Rinto Noviantoro; Sulisti Afriani; Heru Kurniawan (Journal of Research in Business, Economics, and Education, 2020)
The purpose of this study was to determine the analysis of earnings planning in the Business Tahu Tempe Baim Manna in South Bengkulu District. The analytical method used in this research is a quantitative analysis using BEP analysis. From the results of the study, the BEP point in 2019 was achieved in the sales volume of 9,513 prints or Rp. 476,031,532.00 with Contribution Margin Ratio of 0.444 or 44.40%. The level of safety or margin of safety is 57.65%. The company's profit rate reaches 25.60%. Based on the 2019 BEP point, then profit planning can be prepared for 2020. If the Business Tahu Tempe Baim Manna in South Bengkulu District plans a 10% increase in profit from 2019 which is Rp 316,510,850.00, then the level of sales that must be achieved is Rp. 1,188,893,806.00 or 23,759 prints.